Cyclodextrin metal–organic frameworks and derivatives: recent developments and applications. (7th June 2022) - Dummert, Sarah V.; Saini, Haneesh; Hussain, Mian Zahid; Yadava, Khushboo; Jayaramulu, Kolleboyina; Casini, Angela; Fischer, Roland A.
Abstract : In this review, we provide an elaborate overview of the state-of-the-art synthesis, design, properties and applications of cyclodextrin metal-organic frameworks (CD-MOFs), CD-MOF hybrids and materials derived from CD-MOFs. Abstract : While there is a tremendous amount of scientific research on metal organic frameworks (MOFs) for gas storage/separation, catalysis and energy storage, the development and application of biocompatible MOFs still poses major challenges. In general, they can be synthesised from various biocompatible linkers and metal ions but particularly cyclodextrins (CDs) as cyclic oligosaccharides are an astute choice for the former. Although the field of CD-MOF materials is still in the early stages and their design and fabrication comes with many hurdles, the benefits coming from CDs built in a porous framework are exciting. Versatile host-guest complexation abilities, high encapsulation capacity and hydrophilicity are among the valuable properties inherent to CDs and offer extended and novel applications to MOFs. In this review, we provide an overview of the state-of-the-art synthesis, design, properties and applications of these materials. Initially, a rationale for the preparation of CD-based MOFs is provided, based on the chemical and structural properties of CDs and including their advantages and disadvantages. Further on, the review exhaustively surveys CD-MOF based materials by categorising them into three sub-classes, namely (i) CD-MOFs, (ii) CD-MOF hybrids, obtained via combination with external materials, and (iii) CD-MOF-derived materials prepared under pyrolytic conditions. Subsequently, CD-based MOFs in practical applications, such as drug delivery and cancer therapy, sensors, gas storage, (enantiomer) separations, electrical devices, food industry, and agriculture, are discussed. We conclude by summarizing the state of the art in the field and highlighting some promising future developments of CD-MOFs.